Phase behavior of model poly(butadiene 1-3)- block- dimethylsiloxane copolymers - Gomez, Leopoldo Raimundo (2015)
Model diblock copolymers of poly(butadiene-1,3) and poly(dimethylsiloxane) (PB-b-PDMS) of different compositions were synthesized by the sequential anionic polymerization (high vacuum techniques) of butadiene 1,3 and hexamethyl(ciclotrisiloxane), (D3), monomers. The block copolymers were characterized by nuclear magnetic resonance (1H and 13C NMR), size-exclusion chromatography (SEC), Fourier Transform infrared spectroscopy (FTIR), and Small Angle X-ray Scattering (SAXS). SEC combined with 1H-NMR analysis indicate that the PB-b-PDMS copolymers exhibit molar masses between 5000 and 13000 g/mol, narrow polydispersity index (Mw/Mn), and chemical compositions ranging from low to intermediate siloxane content. According to SAXS experiments, at room temperature the model block copolymers present morphological arrangements that vary from disordered and body-centered-cubic packing of spheres, to hexagonally packed cylinders and lamellar structures.